Acesso aberto e os critérios para avaliação dos programas de pós-graduação no Brasil - Borges, Leandro da Conceição (2018)
The so-called "crisis of periodicals", which arises amid the increasing monetary charges of the large commercial publishers to access the signatures of the journals marketed by them, is at the origin of a movement where several actors from the scientific community have gathered for the democratization of scientific information access. The Open Access Movement appears in the late nineties and it is structured in the following decade by applying two main strategies: The journals of open philosophy, the "gold route", and the self-archiving centralized in the digital repositories, the "green route". After almost three decades, although the open access philosophy is widespread and the number of open philosophy journals has grown, a significant part of science is still published in restricted access journals. In Brazil, until very shortly, the responsibility for science was in charge of the research institutes. In recent decades, universities have begun to assume the central role in conducting scientific activities, a phenomenon that is intimately linked to the expansion of the postgraduate system in the country. Since 1990, the Coordination for the Improvement of Higher Education Personnel (Capes) conducts periodic evaluations of the postgraduate programs, which includes, among other criteria, the academic performance of its professors and students, estimating, the periodical where they publish their research studies, and the criteria of this evaluation are guiding elements for the decision-making process for publication of journals. This dissertation aims to verify the occurrence of the term "open access" and similar terms in the journal evaluation documents of Capes. To this end, we analyzed the evaluation documents available on the Capes website, from the 49 areas of knowledge, in the triennial (2010-2012) and four-yearly (2013-2016) assessments, totalling 98 documents. The content analysis was used to categorize the data, according to Bardin, resulting in two blocks of results. Regarding the inclusion of open access in Qualis strata, it was a very low frequency in the highest strata, i.e. A1, A2, B1 and B2; showing frequent occurrences in the large areas of the Humanities, Applied Social Science, Multidisciplinary and Arts and Letters. There were also some mentions of open access in the stratum C, whose journals, according to the Capes evaluation, did not score as conclusions, it was observed that open access is approached in an incipient way in the high strata of the evaluation documents of journals in the areas. It is hoped that the result of this dissertation shows the committees of Capes area that it is necessary to include in their evaluation documents the incentive for publication in open access, since these journals represent to society greater democratization of access to information.